Klasyfikacja form pomocy publicznej stosowanych w Polsce - Bartniczak, Bartosz (Classification of forms in which state aid could be granted in Poland, 2007)
The Act on Conditions for Approving and Supervising Public Support for Entrepreneurs has been in effect in Poland since 2000. The main aim of this article is the analysis of selected forms in which state aid could be granted. The article also presents the classification of this forms. The author suggests which of these forms should be preferred in granting state aid.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 18-25